The Educational Administration of the Elderly Guizhou University, Guizhou Province, People’s Republic of China: The Educational AThe Educational Administration of the Elderly Guizhou University, Guizhou Province, People’s Republic of Chinadministration of the Elderly Guizhou University, Guizhou Province, People’s Republic of China - Shaohua, Zhang; Vajarintarangoon, Kovit; Wongthongcharoen , Bunphot (RATANABUTH JOURNAL, 2025)
The objective of this study was to examine the current state and management of education at universities for the elderly. The sample group consisted of 140 faculty members from Guizhou University for the Elderly, Guizhou Province, People’s Republic of China, determined based on the Krejcie and Morgan table, and cluster sampling. The research instrument used was a questionnaire, with a reliability coefficient of 0.97. Data analysis was conducted using percentage, mean, and standard deviation. Additionally, to explore management strategies, semi structured interviews were conducted with five experts, selected by using purposive sampling. and the data were analyzed using content analysis. The research results revealed that: 1) The overall level of state of education management at universities for the elderly was at a high level ( = 3.76, S.D. = 0.63). 2) The proposed educational management strategies for universities for the elderly include: implementing an intelligent registration system to streamline the student enrollment process. Developing short-term courses that are easy to understand and tailored for elderly learners. Establishing a support center for elderly learners, staffed with experts and volunteers to provide both academic and psychological assistance and utilizing a smart management system to monitor and improve learning facilities, ensuring they were suitable for elderly students.